2021
DOI: 10.1007/s11101-021-09753-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential medicinal effects and applications of stevia constituents

Abstract: The application of stevia glycosides in the food industry has grown steadily in the last two decades. Besides the use of its constituents as natural sweeteners, increasing attention has been given to their potential health benefits and therapeutic applications. Whereas in some cases clinical studies have been realized (prominently, to investigate its hypoglycemic and antihypertensive activity) many of them have failed to cover the expectations from preclinical investigations. Here, we review current knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 85 publications
0
7
0
1
Order By: Relevance
“…However, among them, steviol glycosides raised the most questions about their potential for use in human treatment therapies, mainly due to insufficient in-depth research into their mechanisms of action and inconsistencies in clinical trial results. Talevi (2021) stated that a potential reason for inconclusive outcomes in clinical trials regarding the antidiabetic effects of steviol glycosides lies in their biopharmaceutical and/or pharmacokinetic aspects, such as an intrinsic pharmacological activity [ 107 ]. Therefore, the potential use of these compounds in human therapeutics will require careful selection of the dose, treatment duration, and appropriate route of administration.…”
Section: Discussionmentioning
confidence: 99%
“…However, among them, steviol glycosides raised the most questions about their potential for use in human treatment therapies, mainly due to insufficient in-depth research into their mechanisms of action and inconsistencies in clinical trial results. Talevi (2021) stated that a potential reason for inconclusive outcomes in clinical trials regarding the antidiabetic effects of steviol glycosides lies in their biopharmaceutical and/or pharmacokinetic aspects, such as an intrinsic pharmacological activity [ 107 ]. Therefore, the potential use of these compounds in human therapeutics will require careful selection of the dose, treatment duration, and appropriate route of administration.…”
Section: Discussionmentioning
confidence: 99%
“…For the former, steviol glucuronide is excreted primarily in the feces via the biliary. However, in humans, steviol is excreted in the urine (EFSA, 2010(EFSA, , 2015Talevi, 2022). For example, a human study showed that after an oral administration of stevioside for 72 h, the excretion of steviol metabolites in urine and feces accounted for 62% and 5.2% of the total intake, respectively (Wheeler et al, 2008).…”
Section: Kinetic and Metabolism Studies About Rebaudioside Amentioning
confidence: 99%
“…In addition, many in-depth studies have been conducted to obtain SvGls from stevia leaves, and new technologies have been developed and commercialized to reduce production costs. According to the statistics, the market value of stevia is forecasted to reach approximately 771.5 million US dollars by 2022 (Stevia's global market value, 2017-2022. Currently, rebaudioside A has become the first commercially available SvGls and has been recognized by many consumers.…”
Section: Introductionmentioning
confidence: 99%
“…It is cultivated in many parts of Brazil, China, Thailand, Paraguay, Central America, and India commercially and widely used in foods, beverages, medicine, cosmetics, and many other food industries (Stoyanova et al., 2011 ). Stevia is used for treating several kinds of noncommunicable diseases (NCDs) such as cancer, T2D, hypertension, kidney disease, obesity, dental caries, and oxidative stress and have also shown antimicrobial activity (Ahmad et al., 2020 ; Singh & Rao, 2005 ; Talevi, 2021 ). Some recent studies found that stevia consumption can help to main weight, energy intake, and appetite (Stamataki et al., 2020 ; Stamataki, Scott, et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%